A Parent Education Program for Parents of Chinese American Children With Autism Spectrum Disorders (ASDs): A Pilot Study. (June 2014) - Chiang, Hsu-Min
This study was conducted to examine the effectiveness of a parent education program on decreasing parenting stress and increasing parental confidence and quality of life in parents of Chinese American children with autism spectrum disorders (ASDs). A pre-, posttest group design was used in this study. A total of nine families of Chinese American children with ASDs participated in a 10-week parent education program (including 10-weekly 120-min group sessions). The findings of this study revealed that after receiving the program, parents of Chinese American children with ASDs showed significant reduction in parenting stress, improvement in parental confidence, and improvement in quality of life in physical health and environment domains.